DEVELOPMENT OF AN EDUCATIONAL ONLINE PLATFORM USING GOOGLE SITES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The implementation of an educational resource in the biomedical field through the Google Sites platform is a promising method of providing publicly accessible and high-quality didactic material for students in medical institutions, as well as for practitioners seeking permanent professional competence improvement. This abstract will review the process of designing such a resource, as well as provide recommendations for its optimal use in the interests of both the teaching staff and the student audience.